ANALISIS PENGARUH STRES KERJA DAN MOTIV ASI INTRINSIK TERHADAP KINERJA KARY A W AN DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL PEMODERASI - Haryanti, Ni Putu Premierita; Ardana, I Komang (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 2 Tahun 2014, 2015)
Thi s  study  aims  to  analyze  the moderating  role  of work  experience  on the effect  of work  stress.  The  study was conducted  at  the  Bali  Dynasty Resort   Kuta  with a  sample  of  84 people,   selected  by proportioned  stratified random  sampl ing  method.  Data  were  analyzed  using  Moderated  Regression  Analysis  (MRA).  It  found  that work experience was able to moderate  stress whi le working on the performance of work experience was  not able  to moderate the  influence of  intrinsic  motivation on  performance.  Head  of the company  should  improve employee performance  through opt imal  recruitment not ice  and pay  at tention to  the  work  experience of  the applicants  as  well   as  providing  information  on  employment  status  and  length  of  employment  to  the  people who elected as an employee
Keywords: work stress, intrinsic motivation, work experience, performance